Physical Fitness: Ps Sipangko Football Club Kabupaten Tapanuli Selatan - Parulian, Toktong; Dupri; Ariyanto, Joko; Candra, Oki (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2024)
Physical health and physical fitness have an important role in the world of sport, especially in the context of football clubs. The PS Sipangko football club in South Tapanuli Regency, which has a long history in the world of football, has unique challenges and opportunities in maintaining the physical health of its players. This study aims to measure and analyze the level of physical fitness of the 13 players of the PS Sipangko football club, South Tapanuli Regency and identify the factors that influence this level of fitness. The research method used was a survey and physical measurements involving club players. The data was analyzed statistically to evaluate the level of physical fitness and its relationship to performance on the field. The results showed that the level of physical fitness of players with an average physical fitness test score was 10.80 in the 14-17 interval with a percentage of 38.46%. Judging from the freshness level norms, the category is classified as Medium. These findings provide a deeper understanding of the importance of maintaining physical health in the world of football and highlight the need to pay attention to aspects of physical fitness in the development of football players.